신생혈관녹내장에서 항대사제의 병용 여부에 따른 아메드 장치 삽입술의 수술 성공률 비교 - 임성협; Sung Hyup Lim; 서원문; Won Moon Seo; 박준정; Jun Jeong Park; 윤성욱; Seong Uk Yun (Daihan angwa haghoi jabji, 2011)
목적: 신생혈관녹내장의 치료로 아메드 장치 삽입술 시에 항대사제의 병용 여부에 따른 수술성공률을 비교해 보고자 한다. 대상과 방법: 신생혈관녹내장 환자 중 아메드 장치 삽입술만 시행한 대조군 20안과 술 중 MMC및 술 후 5-FU를 병용한 실험군 20안에서 1) 연속된 3회 방문 시에 안압이 18 mmHg 초과 2) 술 전에 비해 20% 미만으로 감소 3) 술 후 최종 안압 하강제 사용 개수가 술전에 비해 두 가지 이상 감소하지 못한 경우 4) 추가적인 수술을 필요로 한 경우 5) 심각한 합병증이 발생한 경우 중 하나에 해당하면 치료 실패로 정의하여 24개월의 경과관찰 기간 중 치료 성공률과 합병증 발생 유무를 후향적으로 비교하였다. 결과: 술 후 24개월 관찰기간 중 대조군의 누적 성공률은 19.1%, 실험군에서 누적 성공률은 43.7%였으며 두 군 모두에서 심각한 합병증은 발생하지 않았다. 결론: 신생혈관녹내장 치료 시 단순 아메드 장치 삽입술에 비해서 술 중 MMC와 술 후 5-FU의 병용치료를 하였을 때 높은 치료 성공률을 보였다. <대한안과학회지 2011;52(12):1470-1477> Purpose: To evaluate the outcomes of Ahmed valve implantation in neovascular glaucoma patients who received intraoperative mitomycin C (MMC) and postoperative 5-fluorouracil (5-FU) after 24 months of follow-up. Methods: A total of 40 eyes from 40 patients with neovascular glaucoma who received antiglaucomatous medication without previous glaucoma surgery were included in the present study. The patients were divided into 2 groups. The control group (20 eyes) underwent Ahmed valve implantation only and the study group (20 eyes) underwent Ahmed valve implantation and received intraoperative MMC and postoperative 5-FU. Failure was defined as the first occurrence of any of the following: 1) the first of 3 consecutive visits where intraocular pressure (IOP) was over 18 mmHg; 2) 20% IOP reduction from baseline; 3) the final number of topical medications was not reduced by at least two from baseline; 4) the need for additional surgery; or 5) the occurrence of a serious complication. Results: In the control group, the cumulative success rate was 19.1% at 24 months. The cumulative success rate in the study group was 43.7% at 24 months. Serious complications such as endophthalmitis, valve exposure, or prolonged hypotony were not observed. Conclusions: The adjunctive use of intraoperative MMC and postoperative 5-FU with Ahmed valve implantation resulted in a high success rate and good IOP control and did not cause serious complications during the follow-up period. J Korean Ophthalmol Soc 2011;52(12):1470-1477